Advances in aircraft landing gear - Schmidt, R. Kyle (Society of Automotive Engineers, 2015)
The aircraft landing gear system is relatively unique on board an aircraft, it is both structure and machine, supporting the aircraft on the ground, yet providing functions such as energy absorption during landing, retraction, steering, and braking. Advances in Aircraft Landing Gear is a collection of eleven hand-picked technical papers focusing on the significant advancements that have occurred in this field concerning numeric modeling, electric actuation, and composite materials. Additionally, papers discussing self-powered landing gear and more electrical overall aircraft architectures have been included.
Title from PDF title page (SAE Web site, 01/08/2016)
Keywords: Airplanes -- Landing gear.; Airplanes -- Taxiing.; elektronické knihy; electronic books